The Making-of Documentary: An Approximation to some Discourse Intentions and Contemporary Uses - Armando Andrade Zamarripa (Cinéma & Cie)
Based on the theoretical studies that have been published to date regarding the Making- of Documentary — concerning intertextuality, film studies, critical theory, mass communication theory and audiovisual didactics — we explore its specificities as a meta- cinematographic practice that manifests itself when a film accounts for the process of creating another film. The article is divided into three sections: Towards a Definition of the Making-of Documentary, Meta-cinematographic Formats and Functions and Specificities of the Making-of Documentary. In the first, its contemporary definition is proposed; In the following, we establish the distinction between the Making-of Documentary and its predecessors or other contemporary practices; Lastly, we approach its discursive intentions — as a promotional object of the film which it alludes to and of its filmmakers as “authors” — and its current uses, which promote an expansion of cinephilia and self- learning in the viewers.